A Numerical Approach to Analysis of an Environment-Friendly Sn-Based Perovskite Solar Cell with SnO2 Buffer Layer Using SCAPS-1D - Sunirmal Kumar Biswas; Md. Shamsujjoha Sumon; Kushal Sarker; Mst. Farzana Orthe; Md. Mostak Ahmed (Advances in Materials Science and Engineering, 2023)
In this research, we have proposed a Sn-based perovskite solar cell using solar cell capacitance software. The main aim of this study is to develop an environment-friendly and highly efficient structure that can be used as an alternative to other toxic lead-based perovskite solar cells. This work performed a numerical analysis for the proposed (Al/ZnO/SnO2/CH3NH3SnI3/Ni) device structure. The absorber layer CH3NH3SnI3, buffer layer SnO2, and electron transport layer (ETL) ZnO, with aluminium as the front contact and nickel as the back contact, have been used in this simulation. Several analyses have been conducted for the proposed structure, such as the impact of the absorber layer thickness, acceptor density, defect density, series and shunt resistances, back contact work function, and operating temperature. The device simulation revealed that the optimum thickness of the absorber layer is 1.5 μm and 0.05 μm for the buffer layer. The proposed Sn-based perovskite structure has obtained a conversion efficiency of 28.19% along with FF of 84.63%, Jsc of 34.634 mA/cm2, and Voc of 0.961 V. This study shows the upcoming lead-free perovskite solar cell’s enormous potential.